Met de kennis van morgen Toekomstverkennen voor de Nederlandse overheid - van der Duin, Patrick; Snijders, Dhoya (Amsterdam University Press, 2018)
This book is about the role and impact of future explorations in the Dutch government landscape. It presents a diverse range of future explorations and thus shows the broad instruments that advisory councils and public knowledge institutions have developed to deliver future-proof information. The contributions in this publication are from eleven public knowledge institutes and advisory boards that carry out future research themselves and publishing: the Advisory Council for Science, Technology and Innovation (awti), the Central Bureau for Statistics (cbs), the Genetic Modification Committee (cogem), the Central Planning Bureau (cpb), the Royal Dutch Meteorological Institute (knmi), the Netherlands Environmental Assessment Agency (PBL), the Rathenau Institute, the National Institute for Public Health and Environment (rivm), the Social and Cultural Planning Office (scp), the Foundation for the Future of Technology (stt) 1 and the Scientific Council for Government Policy (wrr). On the basis of recent explorations of the future, per chapter as a case be elaborated will be different methods and techniques are presented that they use to get a grip on the future. Here insight is given into the way in which future explorations find their way to the Dutch political decision-making and the impact they have.